Estudo fitoquímico e propriedades biológicas da Dipteryx alata Vogel (baru) - Sanchez, Rodolfo Marcchiori [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Due to the importance of the cerrado biome, including the maintenance of other interconnected biomes in recent decade’s researchers from different fields have proposed alternative use of the cerrado species as a way to preserve the local fauna and flora. One way to help the preservation of species is the study of the medicinal properties of plants of this biome used in traditional medicine. The objective of these studies is to confirm the therapeutic potential and the toxicity of these plants used in traditional local medicine as well as studying the medicinal potential of plants yet to be investigated. The specie Dipteryx alata Vogel (baru) is a native species of the cerrado with great nutritional and pharmacological potential to be investigated, because according to traditional medicine it is used to combat bronchitis, diarrhea, dysentery, pain, sore throat, flu, snakebite, cough and as cicatrizant, however, only the activity against snakebite has been scientifically proven. Therefore, trying to combine the nutritional value of baru fruits pulp to the potential therapeutic effect, studies on the determination of phytochemicals present were performed to guide studies on possible biological properties valuing the fruit as a nutraceutical food in areas of occurrence of the plant that show high negligible diseases indices. The results of the phytochemical studies showed the presence of alkaloids, tannins, flavonoids, saponins and cardiotonic glycosides in considerable amounts and anthraquinones at low concentration. The presence of these phytochemicals has given support for conducting tests to determine the antiparasitic potential. Antimicrobial activity was also evaluated due to the medicinal use of the plant for the urinary tract infections. In addition, the cytotoxicity of the pulp was also evaluated on LLC- MK 2 cells to support the safe use of the fruit. Antimicrobial assays were performed using the bacterial strains Proteus sp., E. ...

Devido à importância do bioma cerrado, inclusive para a manutenção de outros biomas interligados, nas últimas décadas pesquisadores das mais variadas áreas vêm propondo alternativas de uso das espécies do cerrado como forma de preservar a fauna e flora local. Uma das formas para auxiliar na preservação dessas espécies esta o estudo sobre constituintes fitoquímicos e propriedades medicinais de plantas desse bioma usadas na medicina tradicional. O objetivo desse estudo é a confirmação do potencial terapêutico bem como da toxicidade dessas plantas usadas na medicina tradicional local, bem como estudar o potencial medicinal de plantas ainda não investigadas. A espécie Dipteryx alata Vogel (baru) é uma das espécies nativas do cerrado que apresenta grande potencial nutricional e farmacológico a ser investigado, pois segundo a medicina tradicional ela é utilizada no combate à bronquite, diarreia, disenteria, dor, dor de garganta, gripe, picada de cobra, tosse e como cicatrizante, entretanto, apenas a atividade contra picada de cobra foi cientificamente comprovada. Desta forma, na tentativa de aliar o valor nutricional da polpa dos frutos do baru a um possível efeito terapêutico, foram realizados estudos sobre os fitoconstituintes presentes nesta parte da planta, a fim de guiar estudos sobre as possíveis propriedades biológicas valorizando o fruto como um alimento nutracêutico, em áreas de ocorrência da planta que apresentam elevados índices de doenças negligenciadas. Os resultados dos estudos fitoquímicos mostraram a presença de alcaloides, taninos, flavonoides, glicosídeos cardiotônicos e saponinas em consideráveis concentrações e antraquinonas em baixa concentração. A presença desses fitoconstituintes forneceu suporte para a realização de ensaios para a determinação do potencial antiparasitário. A atividade antimicrobiana também foi avaliada devido ao uso medicinal da planta para infecções do trato ...
Keywords: Química vegetal; Plantas dos cerrados; Antioxidantes; Agentes anti-infecciosos; Botanical chemistry